INTERNATIONAL ASPECTS OF EDUCATION AND TRAINING IN TELEMEDICINE - R. Engelbrecht; A. Hasman; J. Mantas; L. Nicholson (Бюллетень сибирской медицины, 2015)
Health care is based on patient data. The doctor, nurse or medical assistant are able by education, training, knowledge and experience to interpret patient data needed for diagnosis and treatment. Health care is dependent on a good education with respect to the management of data, information and knowledge. International activities point to ways to achieve a good level of education. These include criteria for curriculum development and accreditation, quality of information systems, further experience with a comprehensive training concept in England and the 10X10 approach in the United States.